Changes in foot pressure on the ground during mae-geri kekomi (front kick) in karate athlete - case study - W. Cynarski; J. Wąsik; D. Szymczyk; A. Vences de Brito (Physical Education of Students)
Background and Study Aim : Biomechanical analysis of martial art techniques are objective and quantitative method, which may be useful in training practice for the purpose of improving these techniques as well as monitoring and enhancing athletes performance. The aim of this study was to assess selected kinetic parameters and lower limb loading during karate front kick, using force platforms, for both kicking and support leg. Material and Methods : Karate athlete, second dan, black belt holder in Idokan style, participated in this case study. The subject performed front kick in the air (without a physical target), both for his right and left leg, while standing on the force platforms. For the purpose of kinetic data recording two force platforms were used in this study (Kistler force plate, type 9286AA, Kistler, Switzerland). Selected kinetic parameters for kicking and support leg as well as front kick execution time were analysed. Results : Results of our case study revealed higher values of the kinetic parameters for the right leg, comparing to the left leg. This results confirm athlete’s declaration of being right leg dominant. Conclusions : Analysis of selected kinetic parameters may be useful in identifying lower leg laterization (leg dominance), as well as existing asymmetries between the dominant and non-dominant leg in karate and other martial art athletes.